COVID-19 and smoking in Russia: how are hospitalizations, course, and outcomes of coronavirus infection related to tobacco use? - M. G. Gambaryan; M. G. Chashchin; A. V. Kontsevaya; A. Yu. Gorshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To study the relationship between the level of hospitalizations, severe course, and mortality from coronavirus disease 2019 (COVID-19) with the smoking prevalence in Russia for 2020-2021.Material and methods. The article analyzes data on the number of people hospitalized with COVID-19, transferred to the intensive care unit (ICU), and died from COVID-19 in 2020-2021 by age and sex groups in 85 Russian regions from the Federal COVID-19 Registry, as well as data on smoking status, socio-demographic characteristics of the sample for 2020-2021 in 85 Russian regions from the Sample Monitoring of the Population Health sample of the Federal State Statistics Service for the corresponding years. Relationships between the smoking and COVID-19 and severe COVID-19 hospitalization rates with transfer to the ICU and the COVID-19 mortality rate by age and sex groups and federal districts of Russia were analyzed. The assessment was carried out using second-order polynomial regression (quadratic regression). The model quality was determined based on the coefficient of determination (R2) and the F-criterion for the general model.Results. Nonlinear relationships between the studied parameters with a characteristic parabolic dependence were obtained. A significant relationship was found between the prevalence of smoking and the level of severe COVID-19 among men in the age groups of 20-29 years, 50-59 years, 70-79 years (p<0,05). A relationship was found between COVID-19 mortality and smoking rate in men aged 15-19 years (R2=0,15, p=0,049), more significant in women (R2=0,35, p=0,002); in women aged 30-39 years (R2=0,06, p=0,007); in men and women aged 40-49 years and 50-59 with a more pronounced trend; in men aged 60-69 (R2=0,05, p=0,018) and in women as a trend (R2=0,03, p=0,078); in women aged 70-79 and ≥80 years (R2=0,06, p=0,039) with a more pronounced trend in men. Positive associations were found between smoking prevalence and the rate of hospitalization for COVID-19 (R2=0,52, p<0,001) and severe COVID-19 (p=0,011) in the Far Eastern Federal District among men, as well as in the Siberian Federal District (p=0,007) and the Ural Federal District. The relationships between the mortality rate from COVID-19 and smoking frequency in different federal districts demonstrate an inverse parabolic dependence.Conclusion. The relationships between smoking and COVID-19 rates are complex and nonlinear. A deep segmented analysis of these relationships revealed significant associations explaining the contribution of smoking to the rate of hospitalizations and severe outcomes, mortality from COVID-19 in certain age groups of men and women and in various federal districts of Russia. Effective tobacco control measures aimed at reducing smoking are necessary to mitigate the adverse effects of coronavirus infections.